The Influence Of Job Satisfaction, Career Development And Teamwork On Employee Retention In Government-Owned Cultural Destinations - Muhammad Syafri; Jenni Veronika Br Ginting; Feriyadin; Darwis; Balla Wahyu Budiarto (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study is to determine whether job happiness, teamwork, and career advancement have an impact on employee retention. 100 employees made up the study's population. Probability sampling with a simple random sampling category of 60 participants was the sampling technique employed in this investigation. To gather data, the researcher provided a questionnaire. Path analysis is used in this study. According to research findings, career growth has an impact on workers' job happiness. Teamwork has an impact on workers' job happiness. Employee job happiness is simultaneously influenced by career growth and teamwork. Employee retention is affected by career advancement. Employee retention is influenced by teamwork. Employee retention is influenced by job satisfaction. Teamwork, professional growth, and job happiness all have an impact on employee retention. Job satisfaction, which is influenced by career advancement, affects employee retention. Through increased job satisfaction, teamwork affects employee retention.